2017
DOI: 10.24914/jeb.v20i1.518
|View full text |Cite
|
Sign up to set email alerts
|

Determinan dan Stabilitas Ekspor Crude Palm Oil Indonesia

Abstract: We analyze the influence of CPO production, exchange

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…Beberapa hasil penelitian yang mengkaji tentang dampak dari harga dan nilai tukar terhadap permintaan eksport minyak sawit masih menghasilkan temuan yang berbeda atau adanya kesenjangan hasil penelitian (gap). Diantaranya yaitu penelitian yang dilakukan oleh Huda & Widodo (2017) menghasilkan penelitian yaitu dalam jangka pendek dan jangka panjang bahwa variabel harga CPO internasional, nilai tukar rupiah, Term of Trade dan produksi berpengaruh signifikan terhadap variabel ekspor CPO. Selanjuntya Ewaldo (2015) menghasilkan penelitian bahwa secara simultan harga dan nilai tukar berpengaruh signifikan terhadap nilai ekspor akan tetapi secara parsial nilai tukar (kurs) menunjukkan pengaruh tidaksignifikan terhadap nilai ekspor.…”
Section: Kata Kunciunclassified
“…Beberapa hasil penelitian yang mengkaji tentang dampak dari harga dan nilai tukar terhadap permintaan eksport minyak sawit masih menghasilkan temuan yang berbeda atau adanya kesenjangan hasil penelitian (gap). Diantaranya yaitu penelitian yang dilakukan oleh Huda & Widodo (2017) menghasilkan penelitian yaitu dalam jangka pendek dan jangka panjang bahwa variabel harga CPO internasional, nilai tukar rupiah, Term of Trade dan produksi berpengaruh signifikan terhadap variabel ekspor CPO. Selanjuntya Ewaldo (2015) menghasilkan penelitian bahwa secara simultan harga dan nilai tukar berpengaruh signifikan terhadap nilai ekspor akan tetapi secara parsial nilai tukar (kurs) menunjukkan pengaruh tidaksignifikan terhadap nilai ekspor.…”
Section: Kata Kunciunclassified
“…The former researcher (Azizah, 2015) indicates that exchange rate has a negative and significant impact on the value of Indonesian CPO export. Other results come from (Huda, 2017) dan (Ginting, 2013) state that exchange rate has a negative and significant impact on Indonesian export. On the researches exchange rate has a two-way relationship on international CPO trade, meaning when an exchange rate depreciates, while export increases and vice versa.…”
Section: B the Impact Of Exchange Rate Towards Indonesian Cpo Export Valuementioning
confidence: 99%
“…If Rupiah appreciates toward forex, it will reduce the export value while import will increase. It happens because the domestic goods in international market become much more expensive (Huda, 2017).…”
Section: B the Impact Of Exchange Rate Towards Indonesian Cpo Export Valuementioning
confidence: 99%
“…As one of Indonesia's export commodities, CPO will be an important part of international trade and will also have an impact on the IDR exchange rate as a transaction tool (Aprina, 2014). The previous study indicated that world CPO price will affect the exchange rate of a country (Amano & Van Norden, 1998;Ashfahany & Priyatna, 2015;Aziz & Applanaidu, 2017;Buyung et al, 2017;Edwards, 1986;Huda & Widodo, 2017;Iqbal, Hameed, & Devi, 2012;Kohlscheen, Avalos, & Schrimpf, 2016). Conversely, the previous study showed Granger Causality tests do not find any evidence that commodity prices Granger-cause exchange rates (Chen, Rogoff, & Rossi, 2010).…”
Section: Introductionmentioning
confidence: 92%